2008
DOI: 10.1348/135910707x250893
|View full text |Cite
|
Sign up to set email alerts
|

Who does expressive writing work for? Examination of alexithymia, splitting, and repressive coping style as moderators of the expressive writing paradigm

Abstract: Future research should include personality measures in explorations of expressive writing to further understand the boundary conditions of the expressive writing paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
3
26
1
6
Order By: Relevance
“…Thus, social role theory would suggest that researchers examine the intersection of social role and physician visits to see if those with traditionally masculine social roles visit physicians less after writing. This recommendation is consistent with the finding that undergraduates with difficulties describing feelings (88 in all, 62 women) had fewer health visits after expressive writing than after neutral writing (Baikie 2008). Further, a metaanalysis of 30 writing studies that measured health care use that indicated that, in 14 samples involving 1,520 healthy people (60.5% women), writing about trauma relative to writing about a neutral topic reduced health care use such as physician visits (Harris 2006).…”
Section: Social Role Theory Research Recommendationssupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, social role theory would suggest that researchers examine the intersection of social role and physician visits to see if those with traditionally masculine social roles visit physicians less after writing. This recommendation is consistent with the finding that undergraduates with difficulties describing feelings (88 in all, 62 women) had fewer health visits after expressive writing than after neutral writing (Baikie 2008). Further, a metaanalysis of 30 writing studies that measured health care use that indicated that, in 14 samples involving 1,520 healthy people (60.5% women), writing about trauma relative to writing about a neutral topic reduced health care use such as physician visits (Harris 2006).…”
Section: Social Role Theory Research Recommendationssupporting
confidence: 77%
“…Physical benefits include shorter hospital stays (Solano et al 2007); fewer health visits (Baikie 2008;Range and Kovac 2002;Richards et al 2000;Rosenberg et al 2002), physical complaints (Rosenberg et al 2002), or upper respiratory problems (Greenberg et al 1996); less fatigue (Danoff-Burg et al 2006); and, improved immunity (Pennebaker et al 1988), wound healing (Weinman et al 2008), smoking resistance (Ames et al 2007), and therapy progress (Graf et al 2008). Psychological or general benefits include reduced work absence (Francis and Pennebaker 1992); improved college grades (Pennebaker and Francis 1996); faster reemployment (Spera et al 1994); less affective dysfunction (Smyth et al 1999); and, less unique grief , anxiety, and depression (Graf et al 2008).…”
Section: Pennebaker's Writing Paradigmmentioning
confidence: 99%
“…We had hypothesized the opposite, that alexithymia would interfere with the benefits of expressive writing, but the finding is consistent with several other studies (Baikie, 2008; Paez et al, 1999; Solano et al, 2003). Although the alexithymia scale that was used in this study has been tested in 19 different cultures (Taylor et al, 2003), psychological constructs are often confounded by culture-specific variables, and in this sample, the scale may have tapped a construct related more to suppression and inhibition of emotional expression rather than deficits in emotional processing, which is the classic definition of alexithymia.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, although expressive writing is generally considered efficacious, there exists considerable between-study variability in the treatment effects of expressive writing and suggests that the benefits of this procedure may be specific to certain individuals, procedural aspects, or contexts or all [18]. In addition to the main effects of the expressive writing procedure on psychological and physical outcomes, recent work in this area has also explored the parameters of expressive writing [19], including the moderating effects of individual differences [20][21][22].…”
Section: Emotion-regulation Interventions In Clinical Samplesmentioning
confidence: 99%